PELATIHAN PENGGUNAAN APLIKASI DAN SISTEM INFORMASI PENERIMAAN PESERTA DIDIK BARU (PPDB) ONLINE DI SMA NEGERI 1 BARABAI - Yusri Ikhwani; Muhammad Hasbi; Andie Andie (Universitas Islam kalimantan MAB, 2017)
SMA Negeri 1 Barabai is one of the establishments engaged in education requires a source of data and proper data processing in order to create efficiency and accuracy of data that can support operational processes, management and decision-making process with good and proper. Good data processing system makes the information that goes to support all existing activities in agencies or companies.Admission Process Students New (PPDB) in SMA Negeri 1 Barabai for this system used still manual that prospective students in the registration process to enter data by writing on the registration form after the data is written on the registration form, and then recapitulated by the committee PPDB into computer. In the process of data recap this committee is only using Microsoft Excel software in processing the data and not use an information system, because the number of applicants who pretty much is about 900 applicants, so that in the process and if the data input takes quite a bit. Because not everyone can mengguaan application, then conducted training for the use of applications and information systems PPDB this.